DELAYS IN THE INTERNATIONAL SEABED AUTHORITY MINING CODE: INSIGHT FROM TWAIL AND BBNJ FRAMEWORKS - Putri, Ria Wierma; Khanza, Yuga Narazua; Davey, Orima Melati; Sabatira, Febryani (Indonesia Law Review, 2024)
The International Seabed Authority (ISA) plays a crucial role in governing the vast expanses of the ocean floor that lie beyond national jurisdictions, referred to as "the Area" under the United Nations Convention on the Law of the Sea (UNCLOS). Although the ISA has established regulations for deep-sea exploration, it has encountered significant challenges in finalizing a comprehensive mining code for resource exploitation. This ongoing delay underscores the notion that legal development is often catalyzed by broader social changes. To comprehend the factors contributing to this delay, it is essential to consider the historical context of UNCLOS 1982, a framework established during a period when numerous developing nations were asserting their independence. The Third World Approaches to International Law (TWAIL) critiques highlight how international legal frameworks have frequently favored developed nations, complicating the pursuit of a just and equitable mining code. Furthermore, the recent Biodiversity Beyond National Jurisdiction (BBNJ) Agreement, which advocates for equitable access to marine resources, poses additional challenges for the ISA. Developed nations, equipped with advanced technologies, continue to dominate deep-sea resource exploitation, exacerbating the existing technological divide, as illustrated by Indonesia's collaboration with the U.S. NOAA in 2010 to explore its marine territory. Social change typically emerges not merely from value shifts but through the resolution of conflicts that lead to new agreements. This article will attempt to understand why the ISA mining code has been delayed and what this means for international law considering the TWAIL and BBNJ approaches.